Durability of response to VGX-3100 treatment of HPV16/18 positive cervical HSIL. Issue 5 (4th May 2021) - Bhuyan, Prakash K.; Dallas, Michael; Kraynyak, Kim; Herring, Timothy; Morrow, Matthew; Boyer, Jean; Duff, Susan; Kim, Joseph; Weiner, David B.
ABSTRACT: VGX-3100 is an investigational DNA-based immunotherapy being developed as an alternative to surgery and ablation for cervical High-Grade Squamous Intraepithelial Lesion (HSIL) with the aim of preserving reproductive health while treating precancerous disease. Response durability up to 1.5 y following dosing is now reported. Histologic regression and HPV16 and/or HPV 18 (HPV16/18) clearance were previously demonstrated in a randomized, placebo-controlled, double-blind trial and reported for 6 months after the last dose of VGX-3100 or placebo. The presence of HPV16/18, Pap smear diagnoses, and immunogenicity longer-term responses were assessed at 18 months after the last dose. 91% (32/35) VGX-3100-treated women, whose cervical HSIL regressed and avoided excision at 6 months following study treatment completion, had no detectable HPV16/18 at 18 months following treatment completion. These results were comparable to those for women who received placebo and then later underwent surgery. For VGX-3100 recipients who regressed at 6 months following study treatment completion and avoided excision during the trial, Pap testing showed no HSIL recurrence at 18 months following VGX-3100 treatment. VGX-3100-induced cellular immune responses specific for HPV 16/18 E6/E7 remained higher than for placebo control recipients at 18 months. In women with cervical HSIL who responded to VGX-3100 and were able to avoid surgery, clinical outcomes were comparable to the placebo control group which underwent conventional surgical treatment. These findings extend the understanding of the durability of the treatment effect of VGX-3100 up to 1.5 y and support that VGX-3100 could be used as an alternative to surgery.